2010
DOI: 10.1590/s1516-35982010001100023
|View full text |Cite
|
Sign up to set email alerts
|

Feed efficiency of Nellore cattle selected for postweaning weight

Abstract: -Two Nellore herds were compared, one selected for greater postweaning weight and the other, control, selected for average postweaning weight, to evaluate the effects of 29 years of selection on feed efficiency. Sixty Nellore males (41 selected and 19 control) averaging 205 kg and 267 days of age were evaluated in individual pens during performance test.Performance and dry matter intake were used to determine the following feed efficiency traits: feed conversion; residual feed intake; residual gain; partial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Another undesirable outcome from selection for growth traits is the increased cost of maintaining animals, due to increased feed intake. For instance, a study in Nellore cattle reported that animals selected for higher post-weaning BW, despite gaining more weight and better AGR and KR, consumed more metabolizable energy than animals selected based on null selection differential [38]. Moreover, there is a compelling body of evidence that selection for growth traits to improve growth, feed conversion efficiency or both could also increase appetite and feed intake, causing excessive deposition of body fat, with adverse consequences, including decreased milk production [4], [7], [8], [22] and [39].…”
Section: Resultsmentioning
confidence: 99%
“…Another undesirable outcome from selection for growth traits is the increased cost of maintaining animals, due to increased feed intake. For instance, a study in Nellore cattle reported that animals selected for higher post-weaning BW, despite gaining more weight and better AGR and KR, consumed more metabolizable energy than animals selected based on null selection differential [38]. Moreover, there is a compelling body of evidence that selection for growth traits to improve growth, feed conversion efficiency or both could also increase appetite and feed intake, causing excessive deposition of body fat, with adverse consequences, including decreased milk production [4], [7], [8], [22] and [39].…”
Section: Resultsmentioning
confidence: 99%